Dynamic pricing and consumer inertia: An empirical analysis - Ronnie Togar Mulia Sirait; Maretta Ginting; Wan Suryani (Faculty of Economics and Business, University of Muhammadiyah Malang, 2024)
This study aims to examine the impact of dynamic pricing on Gen Z consumer inertia. This study defines consumer inertia as the tendency to continue using the same product or service. In addition to focusing on dynamic pricing, this study also involves several control variables: consumer reviews, loyalty, brand image, and influencer marketing. We use 103 respondents who frequently purchase personal care products from online marketplaces. Through regression analysis using Ordinary Least Squares (O.L.S.), Generalized Least Squares (G.L.S.), and Robust Least Squares (R.L.S.), we found that dynamic pricing and consumer reviews have a significant effect on consumer inertia. Specifically, price reductions on competing products and positive reviews for these items encourage Gen Z to switch brands. In contrast, loyalty, brand image, and influencer marketing do not significantly affect consumer inertia. The findings of this study suggest that brands seeking to capture Gen Z's market share should focus on price competition and product quality transparency instead of building loyalty, brand image, and promoting influencer marketing.